2016
DOI: 10.3389/fneur.2016.00156
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Findings in Post-Concussion Syndrome Patients after Mild Traumatic Brain Injury: A Systematic Review

Abstract: ObjectivesTo review the evidence for the use of diffusion tensor imaging (DTI) parameters in the human brain as a diagnostic tool for and predictor of post-concussion syndrome (PCS) after a mild traumatic brain injury (mTBI).DesignSystematic review.Data sourcesAll relevant studies in AMED, Embase, MEDLINE, Ovid, PubMed, Scopus, and Web of Science through 20 May, 2016.Study selectionStudies that analyze traditional DTI measures [fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), and axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 67 publications
1
53
0
2
Order By: Relevance
“…There have been few reviews summarizing existing literature on structural and functional changes along with behavioural outcomes, including cognitive impairments, neuropsychiatric de cits or symptomology, in patients with persisting post-concussive symptoms. Khong et al 25 , reported that loss of integrity in long white matter tracts such as corpus callosum was the most cited abnormality in PCS literature, which was consistent with a previous review. 17 The current literature in PCS is limited because of a lack of converging knowledge due to few studies published on the topic.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…There have been few reviews summarizing existing literature on structural and functional changes along with behavioural outcomes, including cognitive impairments, neuropsychiatric de cits or symptomology, in patients with persisting post-concussive symptoms. Khong et al 25 , reported that loss of integrity in long white matter tracts such as corpus callosum was the most cited abnormality in PCS literature, which was consistent with a previous review. 17 The current literature in PCS is limited because of a lack of converging knowledge due to few studies published on the topic.…”
Section: Introductionsupporting
confidence: 85%
“…17 The current literature in PCS is limited because of a lack of converging knowledge due to few studies published on the topic. 25 As described, most of the knowledge synthesis in the eld has focused on only one domain: loss of white matter integrity, disruption of functional connectivity or symptoms/behavioural de cits observed in patients with PCS. To our knowledge, there is no systematic summary of literature focused on understanding the structural or functional changes along with cognitive, neuropsychiatric measures or symptom severity in the adult population with PCS.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] Magnetic resonance imaging studies using modern techniques such as diffusion tensor imaging suggest that microstructural pathology (eg, weakened integrity of long white matter tracts) can also be a feature of mTBI, 39 although the nature, location, time course, and clinical significance of such changes are unclear. [40][41][42] Clinical presentation and diagnosis mTBI can be challenging to diagnose in any setting because the acute signs and symptoms of altered mental status (AMS) are often subtle and transient, and available diagnostic tests (eg, CT) are not sensitive. These issues may be compounded in primary care, where patients are often first evaluated days or even weeks after an injury event and factors that mimic mTBI-like symptoms (fig 1) may have emerged.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Acutely following concussion, clinical or behavioral manifestations of white matter alterations may include worse post-concussion symptom severity and poorer cognitive performance (Geary, Kraus, Pliskin, & Little, 2010;HellstrĂžm et al, 2017;Khong, Odenwald, Hashim, & Cusimano, 2016;Womack et al, 2017). A systematic review conducted by Khong and colleagues concluded that decreased FA and increased MD and RD are correlated with greater symptom severity and prolonged post-concussion symptoms (Khong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%